Uji Aktivitas Antibakteri Ekstrak Daun Sambung Nyawa (Gynura procumbens (Lour.) Merr.) terhadap Bakteri Escherichia coli ATTC 25922 : Antibacterial Activity Test of Sambung Nyawa (Gynura procumbens (Lour.) Merr.) Leaf Extract Against Escherichia coli ATTC 25922 - Yasnatasya Ys, Jian; Hakim, Ali Rakhman; Hidayah, Nurul (Indonesian Journal of Pharmacy and Natural Product, 2023)
Diarrhea is a disease that contributes to the highest death rate in Indonesia. The number of diarrhea cases recorded in Indonesia in 2021 was 7.3 million cases. The most common cause of diarrhea is Escherichia coli bacteria. Based on previous studies, one of the traditional medicines that can treat diarrhea is sambung nyawa leaf (Gynura procumbens (Lour.) Merr.) which have various secondary metabolite compounds that can kill bacteria. The purpose of this study was to determine the antibacterial activity of sambung nyawa leaf against Escherichia coli ATTC 25922. The method used for extracting sambung nyawa leaf was using ultrasonic methods. Antibacterial activity testing used the well-diffusion method and the determination of the Minimum Inhibitory Concentration (MIC) and the determination of the Minimum Bactericidal Concentration (MBC) by the dilution method. Test results data were analyzed using the Kruskal-Wallis Test. The results of this research show that sambung nyawa leaf have antibacterial activity through well-diffusion testing with an average inhibition zone at a concentration of 100% of 18.215 mm, a concentration of 75% of 16.02 mm, a concentration of 50% of 14.445 mm, a concentration of 25% of 13.33 mmm. In the MIC test, the minimum inhibition ability was obtained at a concentration of 50%. The results of the Kruskall-Wallis test in the three tests showed that there were significant differences in each treatment group. The conclusion of this research is that sambung nyawa leaf have antibacterial activity against Escherichia coli ATTC 25922 with a MIC value at a concentration of 50%, but no MBC has been found against Escherichia coli ATTC 25922.   ABSTRAK Diare menjadi penyakit yang menyumbangkan angka kematian tertinggi di indonesia. Jumlah kasus diare yang tercatat di Indonesia pada tahun 2021 sebanyak 7,3 juta kasus. Bakteri penyebab diare terbanyak adalah bakteri Escherichia coli. Salah satu obat tradisional yang dapat mengobati diare adalah daun sambung nyawa (Gynura procumbens (Lour.) Merr.) yang memiliki berbagai senyawa metabolit sekunder yang bisa membunuh bakteri berdasarkan penelitian terdahulu. Tujuan dari penelitian untuk mengetahui aktivitas antibakteri daun sambung nyawa terhadap Escherichia coli ATTC 25922. Metode yang digunakan untuk ekstraksi daun sambung nyawa  menggunakan metode utrasonik. Pengujian aktivitas antibakteri menggunakan metode difusi sumuran dan penentuan Konsentrasi Hambat Minimum (KHM) dan penentuan Konsentrasi Bunuh Minimun (KBM) dengan metode dilusi. Data hasil uji dianalsisis menggunakan Kruskal-Wallis Test. Hasil dari penelitian daun sambung nyawa memiliki aktivitas antibakteri melalui pengujian difusi sumuran dengan rata-rata zona hambat pada konsentrasi 100% sebesar 18,215 mm, konsentrasi 75% sebesar 16,02 mm, konsentrasi 50% sebesar 14,445 mm, konsentrasi 25% sebesar 13,33 mm. Pada uji KHM didapatkan kemampuan daya hambat minimum pada konsentrasi 50%. Hasil uji Kruskall-Wallis pada ketiga uji meunjukkan terdapat perbedaan nyata pada masing-masing kelompok perlakuan. Simpulan dari penelitian ini daun sambung nyawa memiliki aktivitas antibakteri terhadap Escherichia coli ATTC 25922 dengan nilai KHM pada konsentrasi 50%, namun belum ditemukan KBM terhadap Escherichia coli ATTC 25922.